Aspirin Reduces Cardiac Interstitial Fibrosis by Inhibiting Erk1/2-Serpine2 and P-Akt Signalling Pathways - Xuelian Li; GuoYuan Wang; MuGe QiLi; HaiHai Liang; TianShi Li; XiaoQiang E; Ying Feng; Ying Zhang; Xiao Liu; Ming Qian; BoZhi Xu; ZhiHang Shen; et al. (Cellular Physiology and Biochemistry, 2018)
Background/Aims: Cardiac interstitial fibrosis is an abnormality of various cardiovascular diseases, including myocardial infarction, hypertrophy, and atrial fibrillation, and it can ultimately lead to heart failure. However, there is a lack of practical therapeutic approaches to treat fibrosis and reverse the damage to the heart. The purpose of this study was to investigate the effect of long-term aspirin administration on pressure overload–induced cardiac fibrosis in mice and reveal the underlying mechanisms of aspirin treatment. Methods: C57BL/6 mice were subjected to transverse aortic constriction (TAC), and treated with 10 mg·kg-1·day-1 of aspirin for 4 weeks. Masson staining and a collagen content assay were used to detect the effects of aspirin on cardiac fibrosis in vivo and in vitro. Western blot and qRT-PCR were applied to examine the impact of aspirin on extracellular signal-regulated kinases (Erks), p-Akt/β-catenin, SerpinE2, collagen I, and collagen III levels in the mice heart. Results: Aspirin significantly suppressed the expression of α-smooth muscle actin (α-SMA; 1.19±0.19-fold) and collagen I (0.95±0.09-fold) in TAC mice. Aspirin, at doses of 100 and 1000 µM, also significantly suppressed angiotensin II-induced α-SMA and collagen I in cultured CFs. The enhanced phosphorylation of Erk1/2 caused by TAC (p-Erk1, 1.49±0.19-fold; p-Erk2, 1.96±0.68-fold) was suppressed by aspirin (p-Erk1, 1.04±0.15-fold; p-Erk2, 0.87±0.06-fold). SerpinE2 levels were suppressed via the Erk1/2 signalling pathway following treatment with aspirin (1.36±0.12-fold for TAC; 1.06±0.07-fold for aspirin+TAC). The p-Akt and β-catenin levels were also significantly inhibited in vivo and in vitro. Conclusions: Our study reveals a novel mechanism by which aspirin alleviates pressure overload-induced cardiac interstitial fibrosis in TAC mice by suppressing the p-Erk1/2 and p-Akt/β-catenin signalling pathways.